The financial and economic crisis and pension systems: International experiences - Frank Eich (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2009)
There has been much discussion in the British general and specialised media over the last year on the adverse consequences of the economic and financial crisis on the British pension system. It should come as no surprise that the crisis has also adversely affected pension systems in most other countries too. This paper contributes to the current debate on pensions in the UK by discussing how pension systems outside the UK have been affected by the economic and financial crisis, and what governments have done to deal with the emerging issues. The paper starts by discussing what theory tells us about the likely impact of this type of crisis on different types of pension systems. While the impact should be more long term in the case of pay-as-you-go state pensions and defined-benefit occupational pensions, theory would suggest that the effects will be felt more immediately in the case of defined-contribution pension schemes or private savings. The paper then goes on to present a number of key developments and policy actions (if any) that have taken place in a select number of countries in the realm of pensions since the onset of the crisis in the second half of 2007. These countries have been chosen as they are representative for a large number of countries, from Chile with its very high dependency on private pensions to Germany, where unfunded social security pensions remain by far the most important source of retirement income. The paper finds that the real world experiences are in line with what could be expected theoretically and argues that regardless of whether a country relies more heavily on an unfunded pay-as-you-go state pension system or funded private pensions (whether defined benefit or defined contribution) the crisis has had an adverse effect everywhere. Existing systems will have to be refined or restructured more fundamentally, with the exact response likely to vary from country to country reflecting society's interpretation of “inter-generational fairness”. Annex A provides information on the respective ageing trends in these countries, while Annex B discusses the respective arrangements set up to protect current and future pensioners' entitlements if and when a pension scheme's corporate sponsor becomes insolvent.
Keywords: 330; Public sector; Private sector; Pension systems; International comparisons; Financial markets; Economic crisis; Defined contributions; Defined benefit